Determinación del impacto de las medidas arancelarias aplicadas al sector de importaciones de la empresa "Repuestos a diesel Francisco Clavijo" - Ruiz Quintero, Estefano Renato (2017)
In the present case analysis, it is tried to demonstrate the effects that have had the tariff measures in the company “REPUESTOS A DIESEL FRANCISCO CLAVIJO” in the years from 2012 to 2016. It starts from the hypothesis that the tariff measures taken by the Ecuadorian government in the last five years have had an impact on the sales revenue of the company. After identifying the problem, it proceeds to request information on sales of the periods from 2012 to 2016, When that information is analyzed, it is decided that the stratified sampling method should be used to obtain a sample and based on the behavior of the sales revenue characteristic in the years from 2013 to 2016 in the sample, to make estimates of the corresponding population parameter for the same years. The work is organized in such a way that once the problem is identified, the background is found which give rise to the posed problem, after defining the objectives we search the literature that helps us to understand in depth the issue raised. The method of analysis from the request data is decided, applying it obtains the necessary findings that allow to conclude that the tariff measures implemented by the government had no effect on the company.